COVID-19 in Refractory Myasthenia Gravis- A Case Report of Successful Outcome - Ramaswamy, Swathi Beladakere (J Neuromuscul Dis, 2020)
This is a brief report of a patient who has refractory Myasthenia Gravis, on multiple long-term immunosuppressive therapies and contracted COVID-19 during this 2020 pandemic. She was quarantined for total of 14 days and recovered successfully without any complications (no myasthenia exacerbation or crisis, no COVID-19 related complications), with no changes to her immunosuppressive therapy. Treatment of MG patients with COVID-19 needs to be tailored to individual patient.